Daily medical education for confined students during coronavirus disease 2019 pandemic: A simple videoconference solution. Issue 6 (22nd April 2020) - Moszkowicz, David; Duboc, Henri; Dubertret, Caroline; Roux, Damien; Bretagnol, Frédéric
Abstract: The outbreak of coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 infection has recently spread globally and is now a pandemic. As a result, university hospitals have had to take unprecedented measures of containment, including asking nonessential staff to stay at home. Medical students practicing in the surgical departments find themselves idle, as nonurgent surgical activity has been canceled, until further notice. Likewise, universities are closed and medical training for students is likely to suffer if teachers do not implement urgent measures to provide continuing education. Thus, we sought to set up a daily medical education procedure for surgical students confined to their homes. We report a simple and free teaching method intended to compensate for the disappearance of daily lessons performed in the surgery department using the Google Hangouts application. This video conference method can be applied to clinical as well as anatomy lessons.